Impacts of Winter and Summer COVID-19 Lockdowns on Urban Air Quality in Urumqi, Northwest China - Mamtimin, Ali; Wang, Yu; Zhao, Tianliang; Sayit, Hajigul; Yang, Fan; Huo, Wen; Zhou, Chenglong; Gao, Jiacheng (Frontiers in Environmental Science, 2022)
Since the COVID-19 pandemic spread around the world, Urumqi in northwest China experienced the wintertime and summertime lockdowns due to COVID-19 epidemics in January and July of 2020. Based on ground and satellite observations, this study assessed the impacts of the two COVID-19 lockdowns on air quality in Urumqi with the seasonal differences. The results showed that PM10, PM2.5, NO2, CO and SO2 levels were reduced by 38%, 40%, 45%, 27%, 8%, respectively, whereas the O3 concentrations increased by 113% during the wintertime lockdown. During the summer lockdown, PM10, PM2.5, NO2, CO and SO2 levels decreased by 39%, 24%, 59%, 2% and 13%, respectively, and the O3 concentrations increased by 21%. During the lockdowns, the NO2 concentrations decreased by 53 % in winter and 13% in summer in the main urban areas, while the NO2 concentrations increased by 23% in winter and 9% in summer in the suburbs. The aerosol optical depth (AOD) decreased by 25 % during summertime lockdown in most areas of Urumqi. Large seasonal differences existed between wintertime and summertime SO2, CO and O3. The lockdown measures played a vital role in the rapid decline of concentrations of the primary air pollutants with the less impacts of meteorological conditions on urban air pollution. The increasing O3 concentrations during the lockdowns reflect a complexity of air quality change caused by O3 concentrations.